Two temperature-induced 1D CuII chain enantiomeric pairs showing different magnetic properties and nonlinear optical responses. Issue 8 (1st February 2023) - Li, Xi-Li; Li, Yanan; Wang, Ailing; Gao, Congli; Cui, Minghui; Liu, Cai-Ming; Zhou, Liming
Abstract : We demonstrate that reaction temperature has a significant impact on the structures of two 1D Cu II chain enantiomeric pairs and subsequently results in their completely distinct magnetic properties and large difference in NLO responses. Abstract : At different reaction temperatures, using Cu(NO3 )2 ·3H2 O to react with enantiomerically pure N-donor ligands (L S /L R ), respectively, two pairs of chiral one-dimensional (1D) Cu II chain enantiomers formulated as [Cu(μ2 -NO3 )(NO3 )(L S )] n /[Cu(μ2 -NO3 )(NO3 )(L R )] n ( S -1-Cu / R -1-Cu, formed at 40 °C with an NO3 − group as a sole bridging ligand) and [Cu(μ2 -L S )(NO3 )2 ] n /[Cu(μ2 -L R )(NO3 )2 ] n ( S -2-Cu / R -2-Cu, formed at 25 °C with L S or L R as a bridging ligand) were prepared, where L S /L R = (+)/(−)-4, 5-pinenepyridyl-2-pyrazine. Interestingly, such a disparity in bridging ligands leads not only to their distinct structural features but also to their completely different magnetic couplings together with a large difference in their nonlinear optical responses. S -1-Cu with a 1D helical structure shows weak ferromagnetic coupling between Cu II ions, while S -2-Cu with a 1D stairway-like structure presents weak antiferromagnetic coupling. In particular, they simultaneously possess both second- and third-harmonic generation (SHG and THG) responses in one molecule with large strength differences. More remarkably, S -1-Cu exhibits a very large THG response (162 × α-SiO2 ), which is 22.5 times that of S -2-Cu, and the SHG strength of S -1-Cu is more than 3 times that of S -2-Cu . This work demonstrates that reaction temperature has a great impact on the self-assembled structures of coordination polymers and subsequently results in their large performance differences.